(3GdeMGSHI GdMchejIs - (3egOj eCehf(B, (3GdMSjfs ((3YeGf(B:s (3OGQ GdGYUGQ GdYdej ddfTQ(B,s, 2017)
(3jJfGhd JWhQ GdacQ GdeMGSHj,GdeYGdLI GdeMGSHjI ddCUhd GdKGHJI aj GdeMGSHI GdMchejI,GdMSGHGJ GdMchejI GdYGeI(B((3GdehGRfI GdYGeI(B)(3,GdJfXjeGJ hGdbhGfjf hGdCfXeI GdeDKQI Ydi GdeMGSHI GdeGdjI GdMchejI,GdejRGfjI GdYGeI ddOhdI heQGMd EYOGOgG,fXGe GdeMGSHI GdMchejI,eaghe GdQbGHI GdOGNdjI heQGMd JWhQgGs
(3HHdjhZQGajG(B:(3U(B.225s
Keywords: (3GdeMGSHI GdMchejIs